Selective Microwave Sintering of EPS Patterns for Lost Foam Casting - Topola, M.; Jastrzębski, K.; Rapiejko, C.; Just, P. (Archives of Foundry Engineering, 2026)
This study investigates an innovative approach to sintering polystyrene via microwave radiation, aiming to transform manufacturing techniques in the lost-foam casting industry. The primary objective was to develop a laboratory-scale method for the microwave-based sintering of polystyrene patterns. Two types of polystyrene were examined: EPS Styropor P 426 Ccycled and EPS K-950w/S4311. The sintering process involved pre-expansion of the material with hot air, followed by placement in a 3D-printed mould, application of a water film as the microwave-absorbing medium (delivered by atomiser both onto the empty mould cavity and onto the bed of pre-expanded beads), and exposure to 2.45 GHz microwave radiation. The key process parameters were the dose of water, the volume of pre-expanded polystyrene, and the duration of microwave sintering. The results showed that longer sintering times enhanced the flexural strength of the patterns: the highest flexural strength of 127.84 kPa was obtained for a flexural specimen produced with 8 ml of water in 20 cm³ of pre-expanded EPS K-950w/S4311 and a microwave exposure time of 480 s (group mean 125.63 ± 2.99 kPa, n = 3). EPS K-950w/S4311 was more amenable to microwave sintering than Styropor P 426 Ccycled. The current findings establish a robust laboratory-scale framework; subsequent research will focus on scaling these parameters for industrial high-volume production and on broadening the statistical sample base. Overall, the proposed microwave sintering technology shows significant promise for the small-batch and prototype production of casting patterns, offering a more environmentally friendly and cost-effective alternative to conventional autoclave-based steam-chest moulding.